Motivation Factors of Participation in Virtual Communities of Practice: The Case of the “Educatefor.life” Community - Arzumanyan, Lusine; Wieder, Charlotte; Tessier, Nathalie; Angué, Katia (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This article explores the drivers of participation in virtual communities of practice based on Deci and Ryan’s self-determination theory (SDT). Our research is based on the study of a virtual international community. The data was collected through 14 semi-structured interviews, direct observation and analysis of documentation. The main findings confirm the importance of competence, autonomy, and relatedness as motivation factors, as in line with SDT, whereas the main contribution is the identification of energizing leader, exclusive resources, and transformative purpose as three additional motivation factors. We have also, differentiated the factors of motivation according to the level of participation in community life (core, active and periphery).